Determination of Mannheimia haemolytica and its macrolide antibiotic resistance genes in fibrinous pneumonia of cattle - Hatipoglu, Fatih; Terzi, Funda; Ates, Mehmet Burak; Balevi, Asli; Ozdemir, Ozgur; Ortatatli, Mustafa (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Early diagnosis and timely initiation of effective treatment are critical for the pneumonic pasteurellosis, which is mostly caused by Mannheimia haemolytica. But recently, strains of M. haemolytica resistant to antibiotics have begun to emerge, making the treatment of infections more difficult. Therefore, it is important to investigate the erm (42), msr (E) and mph (E) genes, which are held responsible for the resistance to antibiotics.The purpose of the present study was aimed to diagnose the presence of M. haemolytica by IHC method from lung tissue samples of young and adult cattle, and calves, also to detect erm (42), msr (E) and mph (E) genes, which are mostly detected in Pasteurella multocida but recently detected in M. haemolytica, by PCR method. In present study, paraffin blocks obtained from 100 young and adult cattle, and calves lung samples, and whose treatment was not responded, were used. Accordingly, the presence of M. haemolytica was detected by IHC in a total 52 cases of in 21 (38%) of the calves, 22 (69%) of the young cattle, and 9 (69%) of the adult cattle. At least one macrolide resistance gene was found by real–time PCR method in 75% of these positive cases. It was thought that the percentage frequency of these genes, which cause resistance by increasing the minimum inhibitory concentrations of macrolide group antibiotics used in the treatment, by high amounts, makes the treatment of infections difficult and causes serious economic losses by causing errors in effective antibiotic selection. Recently, strains of M. haemolytica resistant to antibiotics have begun to emerge, making the treatment of infections more difficult. For this reason, it is recommended that this type of prevalence studies should be renewed periodically due to possible resistance development and the repeated use of antibiotics with resistive shape should be avoided.